Navigating the river(s) of systems change: a multi-methods, qualitative evaluation exploring the implementation of a systems approach to physical activity in Gloucestershire, England. Issue 8 (8th August 2022) - Nobles, James; Fox, Charlotte; Inman-Ward, Alan; Beasley, Tom; Redwood, Sabi; Jago, Russ; Foster, Charlie
Abstract : Objectives: Systems approaches aim to change the environments in which people live, through cross-sectoral working, by harnessing the complexity of the problem. This paper sought to identify: (1) the strategies which support the implementation of We Can Move (WCM), (2) the barriers to implementation, (3) key contextual factors that influence implementation and (4) impacts associated with WCM. Design: A multi-methods evaluation of WCM was completed between April 2019 and April 2021. Ripple Effects Mapping (REM) and semi-structured interviewers were used. Framework and content analysis were systematically applied to the dataset. Setting: WCM—a physical activity orientated systems approach being implemented in Gloucestershire, England. Participants: 31 stakeholder interviews and 25 stakeholders involved in 15 REM workshops. Results: A white-water rafting analogy was developed to present the main findings. The successful implementation of WCM required a facilitative, well-connected and knowledgeable guide (ie, the lead organisation), a crew (ie, wider stakeholders) who's vision and agenda aligned with WCM's purpose, and a flexible delivery approach that could respond to ever-changing nature of the river (ie, local and national circumstances). The context surrounding WCM further strengthened and hampered its implementation. Barriers included evaluative difficulties, a difference in stakeholder and organisational perspectives, misaligned expectations and understandings of WCM, and COVID-19 implications (COVID-19 also presented as a facilitative factor). WCM was said to strengthen cohesion and collaboration between partners, benefit other agendas and policies (eg, mental health, town planning, inequality), and improve physical activity opportunities and environments. Conclusions: This paper is one of the first to evaluate a systems approach to increasing physical activity. We highlight key strategies and contextual factors that influenced the implementation of WCM and demonstrate some of the wider benefits from such approaches. Further research and methodologies are required to build the evidence base surrounding systems approaches in Public Health.